2017
DOI: 10.4269/ajtmh.16-0345
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Short-Course Meglumine Antimoniate (Glucantime®) for Treatment of Visceral Leishmaniasis: A 13-Year, Multistage, Non-Inferiority Study in Iran

Abstract: Abstract. The World Health Organization's (WHO) recommendation is 28-day course of meglumine antimoniate (Glucantime ® , Sanofi Aventis, France) for the treatment of visceral leishmaniasis (VL). The aim of this study was to evaluate the effectiveness of a shorter duration of treatment in regions with low level of resistance to Glucantime. During 13 years, this study was conducted in three phases on 392 patients. In the pilot first phase, we performed splenic punctures in seven patients to assess the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Comparing the demographic data (gender and age) revealed no significant differences between VL patients and controls ( P > .05). The patients were treated with two protocols, as previously described 17,27,28 . Since there were no statistically significant differences in the amounts of IL‐9+CD4+ T cells and the corresponding cytokines, the cumulative data of both therapeutic protocols were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the demographic data (gender and age) revealed no significant differences between VL patients and controls ( P > .05). The patients were treated with two protocols, as previously described 17,27,28 . Since there were no statistically significant differences in the amounts of IL‐9+CD4+ T cells and the corresponding cytokines, the cumulative data of both therapeutic protocols were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the disease was confirmed by the laboratory findings such as anaemia, the presence of amastigote form of Leishmania (Leishman body) in bone marrow aspirates and/or positive serological tests including positive indirect fluorescent antibody (IFA) ≥1/128 against Leishmania parasites or detection of antibody against kinesin related protein K39 (rK39) and also the detection of L infantum DNA in the peripheral blood using real‐time PCR. Based on the guidelines of WHO expert committee, all the patients were treated with 20 mg/kg/day Glucontime up to a maximum of 850 mg for 4 weeks, 17 or treated until one week after defervescence as a short course therapy, previously described by Alborzi et al 27,28 The study was approved by the ethics committee of the Clinical Microbiology Research Center, Shiraz University of Medical Sciences, Shiraz, Iran (IR.SUMS.REC.1398.703). The demographic, laboratory and clinical data are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, shorter courses of up to 21 days have been shown to be efficacious with low levels of treatment failure. 44 , 45 -46 Moreover, this likely explains why no studies from South America were identified, despite ongoing research there.…”
Section: The Influence Of Hiv-1 Statusmentioning
confidence: 99%